Impact of a multi-component implementation strategy to increase outdoor free play opportunities in early childhood education and care (ECEC) services: the get outside get active (GOGA) randomised controlled trial - Sze Lin Yoong; Nicole Pearson; Luke Giles; Hannah Lamont; Luke Wolfenden; Jannah Jones; Christophe Lecathelinais; Patti-Jean Naylor; Anthony Okely; Nicole Nathan; Kathryn Reilly; Rebecca Lorch; et al. (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Increased outdoor free play is associated with health and developmental benefits for preschool-aged children. It is therefore recommended that early childhood education and care (ECEC) services provide increased time for outdoor free play. This study seeks to understand the impact of a multi-component implementation strategy (Get Outside Get Active) on ECEC service provision of opportunities for outdoor free play. Methods This was a parallel-group randomised controlled trial involving 84 ECEC services located in one region of New South Wales, Australia. Forty-one services were randomised to a 6-month multi-component implementation strategy or to a usual care group (n = 43). To increase total scheduled outdoor free play time, services were supported to modify their routines to increase provision of outdoor free play and/or indoor-outdoor free play opportunities (whereby children are allowed to move freely between indoor and outdoor spaces). The primary trial outcome, mean minutes per day of outdoor free play opportunities provided in ECEC services, was measured at baseline, 6-months (primary endpoint), and 18-months. Secondary outcomes were mean minutes of indoor-outdoor free play only and proportion implementing indoor-outdoor free play for the full day. The quality of the movement environment was assessed using direct observations in 30 ECECs at 6 months only. Results At 6 months, the intervention group showed a significant increase in mean daily minutes of outdoor free play (61.3 min; 95% CI 2.5 to 120.01; p = 0.041) and indoor-outdoor free play (59.1 min; 95% CI 9.1 to 109.1; p = 0.021) relative to the control group. However, no significant between-group differences were observed at 18 months. The proportion implementing a full-day indoor-outdoor program (OR 1.97; 95% CI 0.81 to 4.78; p = 0.196) and the quality of movement environments did not differ between groups at 6 months. Conclusions The implementation strategy significantly increased outdoor free play opportunities in ECEC services post-intervention, though the between group effects were not sustained at 18 months. Future research should focus on ensuring the long-term impact of implementation strategies and understanding the factors driving changes in control group behaviour. Trial registration This trial was prospectively registered with the Australian New Zealand Clinical Trials Registry (ACTRN12621000987864).